Phase shift methodology assessment of an automotive mixed flow turbocharger turbine under pulsating flow conditions - Padzillah, M. H. (Penerbit UTM Press, 2015)
The reciprocating nature of an Internal Combustion Engine (ICE) inevitably results in unsteady flow in the exhaust manifold. In a turbocharged engine, it means that the turbine is subjected to highly pulsating flows at its inlet. The finite time taken by the travelling pressure waves necessitates the need for phase-shifting method before any instantaneous parameter can be analyzed. In a turbocharger test-rig where the instantaneous isentropic power is evaluated upstream of the instantaneous actual power, one of the parameter has to be time-shifted in order to obtain meaningful instantaneous turbine efficiency. This research aims to compare two different methods of phase shifting which are by peak power matching and summation of sonic and bulk flow velocity. In achieving this aim, Computational Fluid Dynamics (CFD) models of full stage turbine operating at 20 Hz, 40 Hz, 60 Hz and 80 Hz have been developed and validated. Instantaneous efficiency was calculated at different locations and the order of calculated efficiency throughout the pulse is analyzed. Results have shown that phase shift using summation of sonic and bulk flow velocity indicated more reasonable efficiency values, thus the method could be used with high confidence for analysis involving unsteady turbine performance.